A Case for Horizontal Distribution of Activities between General Surgery and Surgical Super Specialties - Minocha, Vivek R.; Gupta, Sanjay; Gupta, Arun (Annals of the National Academy of Medical Sciences (India), 2023)
Under the current practice in organizing surgical services, proportionate representation of disciplines is provided in the curricular planning and in corresponding clinical functions. This is based on the level of competence expected by the end of training period. The disciplines as a “whole” are placed in general surgery or super specialty. The system of vertical arrangement has some serious concerns. Paradoxically, patients with diseases of simple and routine nature of discipline categorized as super specialty are neglected. Super specialist is unable to attend on account of preoccupation with serious challenging problems. The general surgeon hesitates because of privileging issues, fear of allegations of negligence and litigation. The system of vertical division is based on premise that some disciplines deal with complex procedures and others with only simple and routine nature. This premise is incorrect. Each discipline is a mix of simple and complex cases requiring specialized treatment. Alternate modified organization of surgical service is proposed. Activities of all disciplines are scrutinized according to the level of expected competence by the end of training. Categorization is shifted from the “discipline' to “activities.” Criteria applied for classification of activities are as follows: on completion, the trainee is capable to assume full responsibility-category 1; has gained sufficient experience-category 2; and is conversant with broad understanding of management-category 3. Activities of category 1 from all disciplines are assigned to general surgery and those of category 3 from all disciplines are assigned to respective super specialty. Those in the middle, comprising difficult cases but not requiring specialized training or heavy inputs in equipment, are in category 2. They are assigned to general surgery as additional/optional items, or super specialty, guided by local factors. The scope and practice of general surgery are broadened with a shift from “residual” to “comprehensive” discipline. Advantages, concerns, collateral issues of horizontal distribution of activities, its positive impact on research and education are discussed. It is concluded that the proposed organization of surgical services is a rational, logical, and practical strategy for good-quality surgical care in the society. The super specialists need to be convinced that “taking load off” is good for the specialty.
Keywords: surgery; general surgery; comprehensive surgery; surgical super specialties; rational organization; surgical services